2011
DOI: 10.1007/978-1-61737-979-6_17
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Detection of Human Regulatory T Cells

Abstract: Tregs are absolutely required for the maintenance of self tolerance in mouse and man. Major abnormalities in Treg number or function cause rare but fatal syndromes with autoimmune, allergic and inflammatory features. Whether subtle Treg abnormalities contribute to the pathogenesis of sporadic autoimmune, allergic and immunoinflammatory diseases in man remains controversial. Robust methods for identifying and isolating human Tregs in patients and healthy controls are essential if we are to understand their role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 8 publications
0
28
1
Order By: Relevance
“…We found that intracellular double-staining for FOXP3 and CTLA-4 leads to suboptimal gating strategies, as the two intracellular markers influence each other. Accordingly, it was demonstrated recently that staining for more than one intracellular marker will quench other fluorochromes used [37]. Thus, in present study, data obtained from double-stained samples were not comparable with those obtained from samples stained with FOXP3 or CTLA-4 alone.…”
Section: Discussioncontrasting
confidence: 78%
“…We found that intracellular double-staining for FOXP3 and CTLA-4 leads to suboptimal gating strategies, as the two intracellular markers influence each other. Accordingly, it was demonstrated recently that staining for more than one intracellular marker will quench other fluorochromes used [37]. Thus, in present study, data obtained from double-stained samples were not comparable with those obtained from samples stained with FOXP3 or CTLA-4 alone.…”
Section: Discussioncontrasting
confidence: 78%
“…Several studies demonstrated that low or negative CD127 expression is an excellent biomarker of Treg, particularly in combination with CD25 or Foxp3. In fact, CD127 and CD25 stain allows human Treg enrichment for in vitro functional studies [23, 24]. So far, the combination of CD25, CD127 and Foxp3 expression is considered the best way to distinguish between human Treg and CD4 + Tcon [23].…”
Section: Discussionmentioning
confidence: 99%
“…Treg was defined as CD3 + CD4 + CD25 + CD127 − . 52 At least 0.2 million cells were acquired and analysis using FACSDiva software (BD Biosciences).…”
Section: Intracellular Staining and Flow Cytometry Analysismentioning
confidence: 99%